CROSS CULTURE UNDERSTANNDING AS A SOURCE OF COMMUNCATION MATERIAL AT FOREIGN LANGUAGE COURSE IN MALANG RAYA - Sri Hartiningsih (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Cross culture understanding is really needed for communication in this globalization area as no country denies interaction with other country. As different country, it shows different language used that has own culture so it is necessary to learn cross culture understanding in order not to have misunderstanding as proper expression in one culture may be considered contrary in another culture. Ascross culture understanding is important in communication, it is used as a source of teachingEnglish for communication that is really suitable with the needs of the students to communicate with foreigner although they are different levels of study, department as well as region. The purpose of this research are to describe the cross culture understanding used as material for teaching English for communication in language for communication and  the meaning in foreign language course in Malang Raya. Descriptive qualitative research is used. As it is known the  number of teachers a lot  it will take  purposive sampling so the subject is the teachers at foreign language course. The instruments used are interview and observation as well as questionnaire. The finding shows that cross culture understanding for communication is found for greeting and daily activity that shows its culture while the meaning is quite different among foreign languages and Indonesia. Some of them show the meaning is almost the same but the others are contradiction.